2022
DOI: 10.1111/ans.18116
|View full text |Cite
|
Sign up to set email alerts
|

Does intra‐operative humidification with warmed CO2 reduce surgical site infection in open colorectal surgery? A randomized control trial

Abstract: Backgrounds Surgical site infections (SSI) are a significant cause of postoperative morbidity and mortality, contributing to a considerable financial burden on the healthcare system. Insufflation of the open surgical wound with warm, humidified carbon dioxide (CO2) is a novel measure aimed to reduce SSI. The local atmosphere of warm, humidified CO2 within the open surgical wound is proposed to decrease airborne contamination, bacterial growth, desiccation, and heat loss while improving tissue oxygenation and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…A retrospective study examining patients undergoing laparoscopic colorectal surgery receiving either DC‐CO 2 versus WH‐CO 2 , observed that WH‐CO 2 decreased the incidence of SSI by 66% [49]. A subsequent RCT in open colorectal surgery found patients who received WH‐CO 2 had significantly higher mean core temperature at the end of the procedure and a lower incidence of SSI but this did not reach statistical significance [50]. The physiological mechanism underpinning this relationship is thought to occur due to the hypothermia induced peripheral vasoconstriction which lowers the partial pressure of oxygen in tissues and thus their immune function [49, 51].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A retrospective study examining patients undergoing laparoscopic colorectal surgery receiving either DC‐CO 2 versus WH‐CO 2 , observed that WH‐CO 2 decreased the incidence of SSI by 66% [49]. A subsequent RCT in open colorectal surgery found patients who received WH‐CO 2 had significantly higher mean core temperature at the end of the procedure and a lower incidence of SSI but this did not reach statistical significance [50]. The physiological mechanism underpinning this relationship is thought to occur due to the hypothermia induced peripheral vasoconstriction which lowers the partial pressure of oxygen in tissues and thus their immune function [49, 51].…”
Section: Discussionmentioning
confidence: 99%
“…noticed a significant decrease in infection rates with WH‐CO 2 , but pooled analysis among five studies demonstrated no clinically meaningful difference. In contrast to the RCT which reported reduced rates of SSI, our review consisted only of elective procedures and predominantly laparoscopic surgeries [50]. Therefore, results may not be generalisable to open and emergent colorectal procedures, and this can be an area of future study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies also measured postoperative outcomes such as surgical site infections, anastomotic leak, length of stay, and mortality, although no statistically significant differences were seen 5,17–20 . A recent randomized controlled trial revealed a reduction in surgical site infections from 13% in conventional open surgery to 4.5% in the warm humidified group, and although this was in accordance with laparoscopic studies (5.7% versus 13%), this result was not statistically significant ( P = 0.092) 19,21 …”
mentioning
confidence: 98%
“…In concordance with its use in laparoscopic surgery, studies where warm humidification is used in open surgery also show promising results for maintaining intraoperative normothermia and minimizing peritoneal damage. In these studies, patients who received warm humidification had a greater average mean core temperature, end of surgery core temperature, and were less likely to become hypothermic at any time during the operation 17–19 . When this technique was utilized, peritoneal biopsies revealed a reduction in oxidative damage and apoptosis of cells, and maintenance of cell structure on microscopy 5,20 .…”
mentioning
confidence: 99%